A Randomized Clinical Trial of Selective Laser Trabeculoplasty Versus Argon Laser Trabeculoplasty in Patients With Pseudoexfoliation. Issue 5 (June 2015) - Kent, Shefalee S.; Hutnik, Cindy M. L.; Birt, Catherine M.; Damji, Karim F.; Harasymowycz, Paul; Si, Francie; Hodge, William; Pan, Irene; Crichton, Andrew
<x xml:space="preserve">Abstract</x> Purpose: To evaluate the efficacy of selective laser trabeculoplasty (SLT) versus argon laser trabeculoplasty (ALT) in lowering the intraocular pressure (IOP) in patients with open-angle glaucoma or ocular hypertension secondary to pseudoexfoliation. Design: Multicentered randomized clinical trial. Participants A total of 76 eyes from 60 patients with pseudoexfoliation and uncontrolled IOP were recruited from 5 Canadian academic institutions. Patients with prior laser trabeculoplasty, ocular surgery within 6 months, previous glaucoma surgery, an advanced visual field defect, current steroid use, and monocular patients were excluded. Methods: Eyes were randomized to receive either 180-degree SLT or 180-degree ALT by a nonblocked randomization schedule stratified by center. Main Outcome Measurement: The primary outcome was the change in IOP at 6 months versus baseline and secondary outcomes included change in number of glaucoma medications after laser. Baseline variables included age, sex, angle grade, angle pigmentation, and number of glaucoma medications. Results: Of the 76 eyes, 45 eyes received SLT and 31 eyes received ALT. The overall age was 72.9 years (65% females). The baseline IOPs in the SLT and ALT groups were 23.1 and 25.2 mm Hg, respectively (P=0.03). The IOP reduction 6 months after SLT was −6.8 mm Hg and post-ALT was −7.7 mm Hg (P>0.05). The SLT group had reduced glaucoma medications by 0.16 medications at 6 months and the ALT group had no decrease in medications over the same time period (P=0.59). There were no postlaser IOP spikes in either group. Discussion: ALT and SLT are equivalent in lowering IOP at 6 months posttreatment in patients with PXF.